INNOVATIVE WORK BEHAVIOR ANALYSIS OF MSME EMPLOYEES: THE ROLE OF CREATIVE SELF-EFFICACY, ORGANIZATIONAL CULTURE AND PSYCHOLOGICAL EMPOWERMENT AS PREDICTORS - Setiyawami, Setiyawami; Setyawati, Amelia; Lestari, Deara Shinta; Wakhyuni, Emi; Syamsuddin, Syamsuddin (SULTANIST: Jurnal Manajemen dan Keuangan, 2023)
Technological advances and disruptions in various fields of the economy have resulted in the existence of innovative work behaviors that are urgently needed for business actors. For business actors, understanding employee behavior is very important, with the hope that business actors can predict and create productive employee performance. Related to innovative behavior for employees, it is very crucial for business actors to understand and know the characteristics of each employee at work. The research's main objective is to analyze the effect of creative self-efficacy, organizational culture, and psychological empowerment on innovative work behavior. The sample in this study is 160 employees who work in SMEs which are determined by the convenience sampling approach. Data analysis used the SPSS application by displaying the results of data processing through research instrument tests with validity and reliability tests, multiple regression analysis, coefficient of determination and hypothesis testing. Based on the results of data analysis concluded that creative self-efficacy, organizational culture, and psychological empowerment have a positive and significant effect on innovative work behavior. The research implications inform that the behavior of employees working in the MSME sector can be more innovative, it requires high creative self-efficacy and business actors can provide motivation that encourages them to be enthusiastic at work. In addition, psychological empowerment also needs to be increased by providing psychological support for employees.